Criminal liability omissive of hierarchical superiors in the Final Agreement for ending the conflict and building a stable and lasting peace of 24 November 2016 of Colombia (2017)
The text begins with an analysis about the way that the Final Agreement with the FARC-EP addresses the criminal liability of the hierarchical superiors, making clear the similarities and differences that are expressed in the Rome Statute. Immediately ther